TEKNIK PEMBIBITAN, PEMUPUKAN, DAN PENGENDALIAN HAMA PENYAKIT TANAMAN KOMODITI JERUK SIAM (Citrus nobilis var. microcarpa) DI KECAMATAN SIMPANG EMPAT DAN KECAMATAN PAYUNG, KABUPATEN KARO, SUMATRA UTARA, INDONESIA - Endang Christine Purba; Bambang S. Purwoko (Jurnal Pro-Life, 2019)
Citrus is one of the horticultural commodities that has been a focus of development in 2018. Citrus is the fourth largest commodity in the percentage of Indonesia fruit production in 2014. In 2014, citrus fruit production in Indonesia was 1,785,256 tons or around 9.01% of national fruit production. Karo Regency is a citrus production center in North Sumatra, Indonesia. According to the Direktorat Jendral Hortikultura (2015) the production of citrus commodities was 173.921 tons (53,30%). In 2014, there were 3,150,060 productive citrus trees with a harvested area of ​​7,875 ha and a production of 500,243 tons in North Sumatra. One of the varieties grown by farmers in Karo Regency is Siam. High productivity of siam is certainly also influenced by seedlings, fertilization and controlling the pests. To determine this, research has been conducted on farmers in Simpang Empat and Payung Districts, Karo Regency, North Sumatra, Indonesia. To get quality Siam seeds, farmers in two research locations used Japansche citroen plants as rootstock because they were resistant to disease and drought. Fertilization of siam uses inorganic fertilizer as much as 3-4 months, while organic fertilizer as much as 10 months. The control of pests of siam citrus is done mechanically and chemically. Pests and diseases that usually attack siam are Bractocera spp, black lice, fruit borers, fungus and powdery mildew. Keywords: cultivation, seedling, fertilizer, pest, productivity, orange, Citrus nobilis